LINC-25. BRAF ABERRATIONS IN PEDIATRIC PILOCYTIC ASTROCYTOMAS (PCAs): PREVALENCE AND IMPACT ON CLINICAL OUTCOME. (4th December 2020) - Ramanathan, Subramaniam; Prasad, Maya; Vora, Tushar; Gurav, Mamta; Sahay, Ayushi; Sahu, Arpita; Moiyadi, Aliasgar; Shetty, Prakash; Goda, Jayant Sastri; Krishnatry, Rahul; Gupta, Tejpal; Epari, Sridhar; et al.
Abstract: BACKGROUND: Increasing knowledge on pilocytic astrocytoma (PCA) biology now points towards an aberration in BRAF/MAPK/ERK pathway which has both diagnostic and therapeutic implications. This study was done to note the impact of BRAF aberrations on clinical outcome in childhood PCA. METHODS: FFPE tissues of all childhood PCA diagnosed during 2011–2017 were evaluated for BRAFV600E mutation by Sanger sequencing and KIAA1549 fusion transcripts (16–9;15–9;16-11) by reverse transcriptase polymerase chain reaction. Children undergoing gross tumor resection received no adjuvant treatment. Unresectable tumors (only biopsy) and NF-1 associated PCAs, were treated if clinically indicated. Only patients with documented therapy details/followup were included for analysis. STUDY RESULTS: Ninety-eight patients (median age-7.7yrs; boy:girl ratio-1.4) were included. Major sites were: Cerebellum-37(38%), 3 rd Ventricle-26(27%), Cerebrum-15(15%). While BRAFV600E mutation was noted in 7/89(8%) specimens, BRAF-fusions were found in 34/85(40%). Following surgery/biopsy, 23(24%) and 21(22%) received adjuvant chemotherapy and radiotherapy respectively. The 1-year/3-year/5-year-EFS of the overall cohort was 90.7%/81.3%/67.4% respectively. Cerebellar tumors did better vis-à-vis other sites(5yr-EFS:74.3% v/s 66.4%;p=0.403). The 5yr-EFS of BRAF-fusion positive tumors (34), tumors without any BRAF aberration (40) and BRAFV600E mutant tumors (7) was 84.8%/ 69.6%/ 42.9% (p=0.215). CONCLUSIONS: BRAF-fusion and BRAFV600E mutation were associated with good and poor outcomes respectively. Lack of statistical significance could be attributed to use of radiation as planned therapy in patients from earlier years. Data on BRAF aberrations in PCAs aids decision making regarding adjuvant therapy and choosing appropriate salvage-therapy especially in relapsed/refractory PCAs.